The psychological aspects of electronic sports: Tips for sports psychologists - García-Lanzo, S.; Bonilla, I.; Chamarro, A. (International Journal of Sport Psychology, 2020)
Professional competition in the field of videogames, known as electronic sports (esports), is rapidly growing and sport psychologists are considering providing support to optimize performance. However, psychologists doubt whether esports is an activity of their competence and players (gamers) and coaches know little about how psychologists can help them optimize their performance. The aim of this article is to bring information related to esports and to how sports psychology applies to the context of competitive gaming. The paper begins with an overview of video gaming, tracing the evolution from the first recreational games to the international competitions of today. The article goes on to define esports and to discuss the extent to which they can be considered sports. Next, the article discusses the role of the sport psychologist in esports and offers an overview of the psychological issues worthy of special attention in this field. In addition, the article presents a career model applied to esports. Finally, the authors provide some reflections on the psychological factors involved in esports, highlight the possible roles of sport psychologists, and suggest possible directions for future research and interventions.